2021
DOI: 10.7358/neur-2021-029-saet
|View full text |Cite
|
Sign up to set email alerts
|

The Paced Auditory Serial Addition Task (PASAT): normative data for the Italian population

Abstract: The Paced Auditory Serial Addition Task (PASAT) is a neuropsychological instrument designed to measure attention, working memory and speed of information processing in a complex manner. It is currently used to evaluate different neurological diseases. the purpose of this study was to establish PASAT normative data for the healthy Italian population using the standardized methodology of Equivalents Scores. the brief PASAT auditory version included in the Multiple Sclerosis Functional Composite was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The Symbol Digit Modalities Test (SDMT) (Nocentini et al, 2006) requires quickly associating symbols with numbers, and measures the speed of processing visual information, oculomotor coordination, sustained attention and learning new visual information. The Paced Auditory Serial Addition Task ( Saetti et al, 2021 ) consists in a task in which numbers are presented orally at a rate of 3 seconds and the person must quickly perform serial additions, adding each number to the previous one. The test measures the speed of processing auditory-verbal information, sustained attention in auditory mode, divided attention and verbal working memory.…”
Section: Methodsmentioning
confidence: 99%
“…The Symbol Digit Modalities Test (SDMT) (Nocentini et al, 2006) requires quickly associating symbols with numbers, and measures the speed of processing visual information, oculomotor coordination, sustained attention and learning new visual information. The Paced Auditory Serial Addition Task ( Saetti et al, 2021 ) consists in a task in which numbers are presented orally at a rate of 3 seconds and the person must quickly perform serial additions, adding each number to the previous one. The test measures the speed of processing auditory-verbal information, sustained attention in auditory mode, divided attention and verbal working memory.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of cognitive evaluation of patients with different disease severities, our results showed that although the rate of correct response was lower in all studied groups compared to the healthy individuals in optimal states (i.e., a PASAT score of about 70 to 80% correct answers) (Aliyari et al, 2018 ; Saetti et al, 2021 ; Woods et al, 2018 ), as shown in Fig. 1 (their mean was between 20 and 60% based on the correct response percentage), an improvement was observed during the study and over time.…”
Section: Discussionmentioning
confidence: 68%
“…The split-half reliability of this test was showed that this test shows the validated results of executive functions in various clinical populations and is the useful measurement to correlate with the results from other neuropsychological tests (Saetti et al, 2021 ). However, it should be noted that the results of this test should be used with caution, because its clinical application is limited.…”
Section: Methodsmentioning
confidence: 97%
“…However, a task will engage WM the more the manipulation of the elements is required [ 18 ]. The tests assaying working memory in the battery, listed in order from those that engage working memory the most to those engaging it the least, are as follows: Dual Task [ 26 ], Paced Auditory Serial Addition Test (PASAT) [ 27 ], Corsi Span-Backward, and Digit Span-Backward [ 28 ].…”
Section: Methodsmentioning
confidence: 99%